Analysis of acupoint selection and prescription rules of acupuncture for treatment of stable angina pectoris based on a Traditional Chinese Medicine inheritance calculation platform: A systematic review. Issue 49 (9th December 2022) - Yang, Kaiwei; Zhang, Lili; Li, Bai; Liu, Tingting; Chao, Yuqiao; Li, Wenfeng; Cao, Ruohan; Chen, Shaozong
Abstract : The use of acupuncture to treat stable angina pectoris is increasing popularity. Based on the prevalence of this treatment over the past 20 years, the rule of acupoint selection and prescription were summarized in this study. The China National Knowledge Infrastructure, China Academic Journal Database, Chinese Science and Technology Periodical Database, PubMed and Web of Science were used for literature search clinical studies on acupuncture in the treatment of stable angina pectoris conducted over the past 20 years were identified, 225 studies were included. Prescriptions were entered into the Traditional Chinese Medicine heritage calculation platform and association rule analysis and complex entropy clustering analysis were performed. Of the sixty-seven acupoints were regularly used and PC6, BL15 and RN17 were the most common. Commonly used meridians were the foot sun bladder meridian, Renmai and hand Shaoyin pericardium meridian; Get the basic prescription of PC6, RN17 and BL15and have two new prescriptions: BL15, ST36 and GB39; DU10, DU11 and RN17. All acupoints act on the heart through neural regulation mechanism. There are many clinical practice guidelines worldwide for writing acupuncture into the recommended therapy. Acupuncture has a clear therapeutic effect on stable angina pectoris. In the treatment of stable angina pectoris, all acupoints directly or indirectly act on the heart, dredge meridians and relieve angina symptoms.